“CAUCASIAN” NARRATIVES OF MODERN POLITICS OF MEMORY IN GEORGIA - Kircanov, Maksim Valer'evic (History, Archeology and Ethnography of the Caucasus, 2022)
The purpose of this study is to analyze the Caucasian dimension in the modern Georgian historical politics of memory. The author analyzes the main vectors and trajectories of the development of Caucasian narratives in the modern memorial canon of Georgia. The novelty of the study lies in the analysis of the practices and strategies used by Georgian intellectuals within the framework of the functioning of Caucasian narratives in the modern memorial canon of Georgia as an element of the politics of memory. Methodologically, the article is based on the principles proposed in the framework of the memorial turn in modern interdisciplinary historiography. The article analyzes: 1) the role of political elites and the media in the formation of Caucasian narratives in the politics of memory, 2) features of the performative turn in historical politics, 3) Abkhazian and Ossetian narratives as components of the Caucasian politics of memory in modern Georgia. The article shows both the consolidating and conflict potential of the Caucasian dimension in Georgian historical politics. It is assumed that the Caucasian narratives in the modern memorial canon are predominantly symbolic for solving internal political problems, since the real influence of Georgia in the region is minimized by external factors. The results of the study suggest that the Caucasian narratives in the Georgian politics of memory have become an element of the ideological legitimation of the elites and the promotion of the concept of Georgia’s special role in the Caucasus.
Keywords: Georgia; historical politics; politics of memory; Caucasian narratives; Ossetian narratives; Abkhazian narratives; memorial canon; wars of memory